Loss-of-function and gain-of-function studies refute the hypothesis that tau protein is causally involved in the pathogenesis of Huntington's disease. Issue 12 (6th January 2022) - Mees, Isaline; Li, Shanshan; Beauchamp, Leah C; Barnham, Kevin J; Dutschmann, Mathias; Hannan, Anthony J; Renoir, Thibault
Abstract: Tubulin-associated unit (Tau) is a microtubule-associated protein, whose abnormal phosphorylation and deposition in the brain characterizes a range of neurodegenerative diseases called tauopathies. Recent clinical (post-mortem) and pre-clinical evidence suggests that Huntington's disease (HD), an autosomal dominant neurodegenerative disorder, could be considered as a tauopathy. Studies have found the presence of hyperphosphorylated tau, altered tau isoform ratio and aggregated tau in HD brains. However, little is known about the implication of tau in the development of HD pathophysiology, which includes motor, cognitive and affective symptoms. To shine a light on the involvement of tau in HD, our present study aimed at (i) knocking out tau expression and (ii) expressing a transgene encoding mutant human tau in the R6/1 mouse model of HD. We hypothesized that expression of the mutant human tau transgene in HD mice would worsen the HD phenotype, while knocking out endogenous mouse tau in HD mice would improve some behavioral deficits displayed by HD mice. Our data suggest that neither the expression of a tau transgene nor the ablation of tau expression impacted the progression of the HD motor, cognitive and affective phenotypes. Supporting these behavioral findings, we also found that modulating tau expression had no effect on brain weights in HD mice. We also report that expression of the tau transgene increased the weight of WT and HD male mice, whereas tau ablation increased the weight of HD females only. Together, our results indicate that tau might not be as important in regulating the onset and progression of HD symptomatology as previously proposed.